Influence of hydrodynamic condition on 1, 3, 5-tris(4-methoxyphenyl)-1, 3, 5-triazinane as a novel corrosion inhibitor formulation for oil and gas industry. (17th February 2021) - Onyeachu, Ikenna B.; Chauhan, Dheeraj Singh; Quraishi, M. A.; Obot, I. B.
ABSTRACT: The present work reports the application of 1, 3, 5-tris(4-methoxyphenyl)-1, 3, 5-triazinane for the inhibition of X60 steel corrosion in 3.5% NaCl saturated with CO2 . The compound was synthesized using a facile ultrasonic irradiation method, and for the first time, a comparative analysis of the static and hydrodynamic conditions was performed. The results of open circuit potential (OCP) vs. time and the potentiodynamic polarization are presented herein. The inhibitor showed a better performance (>97% efficiency) in the hydrodynamic conditions compared to the static conditions (>90% efficiency). The OCP vs. time results indicated a negative shift of the potential with inhibitor, revealing a primarily cathodic-type mechanism. Potentiodynamic polarization showed that the introduction of the triazine derivative significantly lowered the corrosion current densities suggesting that the inhibitor acted by adsorption and exhibited a mixed type of inhibition behavior with predominance of cathodic effect. The inhibitor adsorption on the steel surface followed the Langmuir isotherm.